Cooperatives Research Trends in Indonesia: A Systematic Literature Review - Hari Sulistiyo; Nugraha Nugraha; Nanu Hasanuh; Sri Suartini; Gusganda Suria Manda; Solihin Sidik; Carolyn Lukita (Universitas Hayam Wuruk Perbanas, 2025)
ABSTRACT This research aims to explore the concept of structure and evolution of literature related to research trends on the topic of cooperatives in Indonesia. This research uses systematic literature observation (SLR) which focuses on findings from various studies that have been published in SINTA indexed scientific journals in Indonesia. Based on predetermined criteria, we used and analyzed 106 articles from 2021 to 2024. The decline in the number of articles about cooperatives over the last four years indicates a shift in focus or interest among researchers, thus indicating the need to re-raise the importance of cooperatives in economic and social development in Indonesia. The results of this study indicted that Regression analysis dominated quantitative research with 26 studies, followed by descriptive analysis with 10 studies. Descriptive analysis was also prominent in qualitative research with 31 studies. System analysis was applied to 3 quantitative studies and 4 qualitative studies, while the research desk was dominant in qualitative research with 11 studies. Other types of analysis used in quantitative research include AHP (1), BSC (1), data mining (1), panel data (2), gross up method (1), PATH (2), SEM (4), and case study (1). Cooperatives play an important role in the economy through human resource development, financial literacy, and the adoption of digital technology, as well as offering alternatives to sharia finance that are in line with Islamic principles. In the social aspect, cooperatives empower vulnerable groups, support entrepreneurship, and provide social assistance, increasing social stability and alleviating poverty. From the results of this research, it is recommended to researchers that to reverse the downward trend in research, strategic steps such as seminars, financial incentives, and institutional cooperation can be taken to generate interest in research on cooperatives.